Combined Rhodiola rosea and eccentric training boost endurance performance and lower-limb reactive strength in recreationally active women - Wang, I-Lin; Su, Yu; Zhang, Long; Tang, Maobing; Chen, Yi-Ming (Frontiers in Physiology, 2025)
This study aimed to determine whether chronic Rhodiola rosea (salidroside) supplementation augments neuromuscular and metabolic adaptations to flywheel eccentric (ECC) training. In total, 30 recreationally active female students were randomly assigned to (1) sedentary placebo control (SC, n = 10), (2) ECC training + placebo (ECC, n = 10), or (3) ECC training + salidroside (150 mg day−1; ECC + SA, n = 10) for 4 weeks. Pre- and post-intervention assessments included exhaustive cycling time to volitional fatigue, peak oxygen uptake (VO2 max), drop vertical jump (DJ) reactive strength index (RSI), and blood biomarkers of muscle damage and metabolism. ECC and ECC + SA prolonged time to exhaustion by 33% and 45%, respectively, without altering VO2 max. Across DJ1–DJ160, RSI significantly increased in both ECC groups (p < 0.01). Salidroside conferred an additional 8%–33% RSI advantage during the final 40 contacts (DJ120–DJ160; p < 0.05). The ECC + SA group exhibited lower postcycling creatine kinase (CK) and higher free fatty acids (FFA) than the SC group (p < 0.05). Triacylglycerol and low-density lipoprotein cholesterol decreased in ECC + SA compared with SC (p < 0.05), whereas body composition remained unchanged. In conclusion, four weeks of ECC training improved endurance and stretch–shortening performance. Salidroside further enhanced late-stage RSI, with additive antifatigue and muscle-protective effects during high-load eccentric conditioning in recreationally active women.